ПОНЯТТЯ ТА ОЗНАКИ ЗЛОЧИННОСТІ ЯК СОЦІАЛЬНО-ПРАВОВОГО ЯВИЩА - Черкасський, Руслан Анатолійович (SUPREMANCE OF LAW, 2017)
The article, based on the analysis of scientific views of scientists, offers an author’s definition of “crime”. Emphasis is placed on the legal and social nature of crime as a phenomenon. The list of key features that characterize crime as a socio-legal phenomenon is highlighted. It is emphasized that the important task of any state is to combat and prevent crime.
Keywords: crime; phenomenon; public danger; social nature